Oligodendrogliogenic and neurogenic adult subependymal zone neural stem cells constitute distinct lineages and exhibit differential responsiveness to Wnt signalling - Ortega, Felipe; Gascon, Sergio; Masserdotti, Giacomo; Deshpande, Aditi; Simon, Christiane; Fischer, Judith; Dimou, Leda; Lie, Dieter Chichung; Schroeder, Timm; Berninger, Benedikt (Nature Cell Biology, 2013)
The adult mouse subependymal zone (SEZ) harbours adult neural stem cells (aNSCs) that give rise to neuronal and oligodendroglial progeny. However it is not known whether the same aNSC can give rise to neuronal and oligodendroglial progeny or whether these distinct progenies constitute entirely separate lineages. Continuous live imaging and single-cell tracking of aNSCs and their progeny isolated from the mouse SEZ revealed that aNSCs exclusively generate oligodendroglia or neurons, but never both within a single lineage. Moreover, activation of canonical Wnt signalling selectively stimulated proliferation within the oligodendrogliogenic lineage, resulting in a massive increase in oligodendrogliogenesis without changing lineage choice or proliferation within neurogenic clones. In vivo activation or inhibition of canonical Wnt signalling respectively increased or decreased the number of Olig2 and PDGFR- ? positive cells, suggesting that this pathway contributes to the fine tuning of oligodendrogliogenesis in the adult SEZ.
EVALuna2:26320